Analysis of damage in composite laminates with embedded piezoelectric patches subjected to bending action. (15th October 2018) - Lampani, L.; Sarasini, F.; Tirillò, J.; Gaudenzi, P.
Abstract: Smart materials offer the possibility of the integration of active functions into a composite primary structure. This work aim to investigate the impact of the incorporation of smart materials in a conventional composite laminate. Fiberglass specimens with and without PZT piezo elements embedded in the lamination stack are manufactured and then subjected to a four-point bending test. Together with the classical mechanical parameters, the operational behaviour of the piezo as sensor is monitored in terms of electrical capacity during test. Benefits and disadvantages of the embedment of a piezo element in a laminate are evidenced from a comparison of the experimental results. In parallel, numerical models of the experimental setup and test, with a finite element approach, allows to explore the mechanisms of damage of such kind of sensorized specimens.